The Security Challenges of The Cooperation Council for the Arab States of the Gulf in Light of International Changes (قضايا سياسية, 2022)
There is a varying increase in the size and type of risks and challenges facing the countries of the Arab Gulf region, which calls for raising the degree of security and military preparedness among its six countries and restoring confidence in the political relations between their regimes. The study aimed to identify the nature of internal and external security threats and challenges to the Gulf Cooperation Council countries. It is difficult to describe the nature of the security challenges facing the Cooperation Council for the Arab States of the Gulf, in addition to the most important strategies that the Gulf countries have put in place to confront them, and whether they were sufficient to confront those challenges and security. threats.